THE SOCIAL RESPONSIBILITY OF A BIG CORPORATE HOUSES - Dr. Neelam Chakrawarti (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2022)
: In recent years, thoughtful corporate social responsibility and exacting social corporate responsibility treatment on the rise countries have become increasingly important. However, many of these studies neglect to look at all of the related factors that affect social corporate responsibility and coverage in those countries, instead focusing on theories and hypotheses established by others. As a consequence, it is their spiritual responsibility to contribute to the growth of the community to which they belong. Companies have recognized that in order to reap measured profits and maintain production, they must priorities public health and reduce social inequalities. As a result, they must be more concerned about society and ordinary citizens. Corporate social responsibility is a mechanism for achieving corporate goals. Key words: -Corporate Social Responsibility, Society, Stakeholders, Indian Companies.